The Role of Organizational Agility and Innovation Capabilities as Mediators in Improving Sustainable Performance through Digital Transformational Leadership - Putra, Ida Bagus Udayana; Udayana, Ida Bagus Nyoman; Putra, Ida Bagus Gede Parama; Saputra, Komang Adi Kurniawan (International Journal of Social Science and Business, 2025)
This study examines the impact of digital transformational leadership on organizational agility, employee engagement, innovation capability, and sustainable performance, with a focus on the mediating roles of these variables. The findings aim to provide practical insights for organizational leaders to enhance sustainable performance through effective digital leadership strategies. The research involved 151 employees from manufacturing companies in Central Java and DIY, selected using purposive sampling. Data were collected via a Likert scale questionnaire (1-5) and analyzed using structural equation modeling (SEM) with AMOS. The results indicate that organizational agility and innovation capability significantly and positively influence sustainable performance, highlighting their critical roles in maintaining long-term competitiveness. However, employee engagement did not show a significant direct impact on sustainable performance. Digital transformational leadership was found to indirectly enhance sustainable performance through its positive effects on organizational agility and innovation capability, rather than through a direct relationship. The study underscores the importance of digital transformational leadership in fostering organizational agility and innovation. Leaders should align digital strategies with adaptive organizational cultures to maximize the benefits of digital transformation. Future research should explore additional mediating factors to further elucidate these relationships.